A randomised controlled trial of an intervention to facilitate the implementation of healthy eating and physical activity policies and practices in childcare services. Issue 4 (17th April 2014) - Jones, Jannah; Wolfenden, Luke; Wyse, Rebecca; Finch, Meghan; Yoong, Sze Lin; Dodds, Pennie; Pond, Nicole; Gillham, Karen; Freund, Megan; McElduff, Patrick; Wye, Paula; Wiggers, John
Abstract : Introduction: Childhood overweight and obesity tracks into adulthood, increasing the risk of developing future chronic disease. Implementing initiatives promoting healthy eating and physical activity in childcare settings has been identified as a priority to prevent excessive child weight gain. Despite this, few trials have been conducted to assess the effectiveness of interventions to support population-wide implementation of such initiatives. The aim of this study is to assess the effectiveness of a multicomponent intervention in increasing the implementation of healthy eating and physical activity policies and practices by centre-based childcare services. Methods and analysis: The study will employ a parallel group randomised controlled trial design. A sample of 128 childcare services in the Hunter region of New South Wales, Australia, will be recruited to participate in the trial. 64 services will be randomly allocated to a 12-month implementation intervention. The remaining 64 services will be allocated to a usual care control group. The intervention will consist of a number of strategies to facilitate childcare service implementation of healthy eating and physical activity policies and practices. Intervention strategies will include implementation support staff, securing executive support, consensus processes, staff training, academic detailing visits, performance monitoring and feedback, tools and resources, and a communications strategy. The primary outcome of the trial will be the prevalence of services implementing all healthy eating and physical activity policies and practices targeted by the intervention. To assess the effectiveness of the intervention, telephone surveys with nominated supervisors and room leaders of childcare services will be conducted at baseline and immediately postintervention. Ethics and dissemination: The study was approved by the Hunter New England Human Research Ethics Committee and the University of Newcastle Human Research Ethics Committee. Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: Australian Clinical Trials Registry ACTRN12612000927820.